Fungal Infective Endocarditis Post Device Occlusion in Perimembranous Ventricular Septal Defect - Sadiq, Nadeem; Haq, Intisar-Ul-; Rafique, Saima; Ullah, Maad; Akhtar, Khurram; Akbar, Hajira; Ara, Andaleeb; Imtiaz, Sana; Farhan, Muhammad Asad; Ahmed, Tufail (Pakistan Armed Forces Medical Journal, 2022)
Recent increase in deployment of trans-catheter devices such as septal or ductal occluding coils and devices has been a possible risk factor for infective endocarditis, predominantly in the initial post deployment period before endothelialization has ensued. Though a long-term study of trans-catheter Atrial Septal Defect (ASD) closure revealed no cases of Infective Endocarditis, some case reports of endocarditis in trans-catheter device closure of ASD, VSD and Patent ductus arteriosus(PDA) advocate that residual defect after device occlusion may be a factor in the risk for Infective Endocarditis. We herein describe the case of a 9-month-old female patient who underwent device closure for peri-membranous ventricular septal defect (VSD) and developed fungal infective endocarditis in early post occlusion period which was confirmed on blood culture. Despite treatment with appropriate antifungal as per sensitivity, clinical condition of the patient deteriorated and it was decided to manage her with surgical explanation of device and closure of defect.